2009
DOI: 10.4149/neo_2009_02_96
|View full text |Cite
|
Sign up to set email alerts
|

L-17 family cytokines in neutrophils of patients with oral epithelial squamous cell carcinoma

Abstract: biobran, enzymatically modified arabinoxylan from rice bran was tested for its possible effects on in vitro maturation of human dendritic cells (DC). immature DC (iDC) derived from plastic-adhered, il-4 and GM-CSF treated peripheral monocytes (Mo) were further cultured with cytokine maturation mix 1 (CMM1; TNF-α, il-1β and il-6) or CMM2 (lPS and iFN-γ) to induce their maturation into mature DC (matDC1 or matDC2, respectively). Different concentrations of biobran (10, 100, 400 and 1000 µg/ml) were applied in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
0
19
1
Order By: Relevance
“…Moreover, neutrophils isolated from the blood of non-CF and CF-patients gave comparable results: IL-17A could decrease the apoptosis in non-CF patients but not in CF patients. Recently Pelletier et al [28] discussed that neutrophils lack the IL-17R receptor and consequently IL-17A could not directly activate neutrophils; however, others proved the presence of IL-17R on neutrophils [29] and Th17 cells could also activate neutrophils through the release of GM-SCF, interferon-γ or TNF-α [16,30]. In the tissue single cell suspension from non-CF patients we found a clear effect on the survival of neutrophils after adding IL-17A, a Th17 cell product.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, neutrophils isolated from the blood of non-CF and CF-patients gave comparable results: IL-17A could decrease the apoptosis in non-CF patients but not in CF patients. Recently Pelletier et al [28] discussed that neutrophils lack the IL-17R receptor and consequently IL-17A could not directly activate neutrophils; however, others proved the presence of IL-17R on neutrophils [29] and Th17 cells could also activate neutrophils through the release of GM-SCF, interferon-γ or TNF-α [16,30]. In the tissue single cell suspension from non-CF patients we found a clear effect on the survival of neutrophils after adding IL-17A, a Th17 cell product.…”
Section: Discussionmentioning
confidence: 98%
“…Because IL-17RB + subsets could be distinguished based upon the intensity of Gr-1 expression, and in light of the differing capacity for IL-4 and IL-13 production between Gr-1 mid and Gr-1 hi populations, IL-17RB + Gr-1 hi cells may have functions that overlap with other CD11b + Gr-1 + populations, such as myeloid suppressor cells 39,40 . A recent study reported that both IL-17RA and IL-17RB can be expressed on the surface of human neutrophils 41 . Clinical studies of patients with steroid resistant asthma demonstrated that a neutrophilic inflammatory response is predominant, while animal studies have suggested that steroid resistant Th17 cells may explain neutrophil-mediated responses 4250 .…”
Section: Discussionmentioning
confidence: 99%
“…The role of metalloproteinases in the progression of human malignancies has been well documented in numerous reports [63,64]. Likewise, some authors have reported new aspects of the biological role of IL-17 family cytokines, as well as indicators of leukocyte activity in IL-17A and IL-17E-dependent reactions in patients with oral epithelial squamous cell carcinoma [65].…”
Section: Bmentioning
confidence: 99%